2011
DOI: 10.1111/j.1095-8312.2011.01616.x
|View full text |Cite
|
Sign up to set email alerts
|

The Amazon River system as an ecological barrier driving genetic differentiation of the pink dolphin (Inia geoffrensis)

Abstract: The pink dolphin (Inia geoffrensis) is widely distributed along the Amazon and Orinoco basins, covering an area of approximately 7 million km 2 . Previous morphological and genetic studies have proposed the existence of at least two evolutionary significant units: one distributed across the Orinoco and Amazon basins and another confined to the Bolivian Amazon. The presence of barriers in the riverine environment has been suggested to play a significant role in shaping present-day patterns of ecological and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 67 publications
2
21
0
3
Order By: Relevance
“…; Hollatz et al . ). Possible reasons for discordant patterns between markers include differences in the dispersal patterns of males and females (Eizirik et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Hollatz et al . ). Possible reasons for discordant patterns between markers include differences in the dispersal patterns of males and females (Eizirik et al .…”
Section: Resultsmentioning
confidence: 97%
“…; Hollatz et al . ); differences between pollen vs. seed dispersal rates (Caetano et al . ; Palma‐Silva et al .…”
Section: Resultsmentioning
confidence: 99%
“…If females were dispersing, lack of structure between populations would be expected when analyzing mitochondrial and microsatellite data, while male dispersal and female philopatry would show population structure for mitochondrial data, but none or lesser levels of structure for microsatellites data, as has been reported for other aquatic mammals (i.e., Amazon river dolphin [ Inia geoffrensis ], Hollatz et al 2011; sperm whales [ Physeter macrocephalus ], Lyrholm et al 1999; dusky dolphins [ Lagenorhynchus obscurus ], Cassens et al 2005; and Dall’s porpoise [ Phocoenoides dalli ], Escorza-Treviño & Dizon 2000 [57], [58], [59], [60]). Microsatellite data presented high homozygote frequencies for all populations of T. manatus and T. inunguis , which supported the presence of null alleles and deviations from HWE.…”
Section: Discussionmentioning
confidence: 68%
“…However, the shape of this relationship may be complex. Many empirical studies have demonstrated that dispersal can be impeded by significant biotic (e.g., behavioural) and/or abiotic (e.g., physical) barriers (Hollatz et al., ; Vallinoto et al., ). These boundaries may result in fine‐scale genetic structure within populations and which is consistent with the hypothesis of isolation‐by‐barriers (IBB).…”
Section: Introductionmentioning
confidence: 99%
“…However, the shape of this relationship may be complex. Many empirical studies have demonstrated that dispersal can be impeded by significant biotic (e.g., behavioural) and/or abiotic (e.g., physical) barriers (Hollatz et al, 2011;Vallinoto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%